The wicked king - Black, Holly (Little, Brown and Company, 2019)
Jude, seventeen and mortal, is now the power behind the Faerie throne, with Cardan as her puppet. As the defacto ruler, court intrigues plague her, and Cardan is more interested in the celebrity than actually taking initiative to lead. Then, a plot against Jude's life comes from someone close to her, and Jude must find the traitor before she loses everything she loves. All the while, she contemplates her increasingly confusing feelings for Cardan.